2007
DOI: 10.1016/j.ydbio.2006.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Islet 1 is expressed in distinct cardiovascular lineages, including pacemaker and coronary vascular cells

Abstract: Islet1 (Isl1) is a LIM homedomain protein that plays a pivotal role in cardiac progenitors of the second heart field. Here, lineage studies with an inducible isl1-cre demonstrated that most Isl1 progenitors have migrated into the heart by E9. Although Isl1 expression is downregulated in most cardiac progenitors as they differentiate, analysis of an isl1-nlacZ mouse and coimmunostaining for Isl1 and lineage markers demonstrated that Isl1 is expressed in distinct subdomains of the heart, and in diverse cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
343
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(375 citation statements)
references
References 36 publications
31
343
1
Order By: Relevance
“…Remarkably, expression of several other genes involved in heart development is observed in myocardial and neural crest lineages, and in the endoderm, including Isl1 (Sun et al, 2007;Cai et al, 2003) and Tbx3 (Mesbah et al, 2008a). Additionally, Id2 was observed in components of the ventricular cardiac conduction system, as described previously (Moskowitz et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Remarkably, expression of several other genes involved in heart development is observed in myocardial and neural crest lineages, and in the endoderm, including Isl1 (Sun et al, 2007;Cai et al, 2003) and Tbx3 (Mesbah et al, 2008a). Additionally, Id2 was observed in components of the ventricular cardiac conduction system, as described previously (Moskowitz et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, in Ciona intestinalis, a prim itive chordate, a fraction of Mesp1 expressing cells coexpresses Isl1 (Stolfi et al, 2010), suggesting that the expression of Isl1 in a subpopulation of the Mesp1 field has been conserved through out vertebrate evolution. In vertebrates, several recent studies showed that Isl1 is expressed transiently in the progenitor of the FHF during embryonic development, and some Isl1 derived cells can give rise to both FHF and SHF derivatives (Brade et al, 2007;Prall et al, 2007;Sun et al, 2007;Ma et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…22 Laugwitz et al 23 demonstrated the presence of an Isl-1 + population of cardiac stem cells in the postnatal mouse, rat, and human heart, most prominently in the outflow tract and right atrium. Further studies showed that Isl-1 marks a population of multipotent cardiac stem cells contributing to smooth muscle, endothelial, and pacemaker cell lineages in the embryonic and postnatal heart 24,25 and implicate Isl-1 + Nkx2.5 + Flk-1 + cells as the most primitive cardiac stem cells. No compelling evidence for an Isl-1 + population in the adult heart has been presented.…”
Section: Isl-1 + Cardiac Stem Cellsmentioning
confidence: 99%